The Accuracy of Third-Trimester Ultrasound in Predicting Large for Gestational Age or Macrosomic Fetuses in Diabetic and Non-Diabetic Pregnant Women: A Systematic Review and Meta-Analysis - Sofia Bussolaro; Vincenza Cofini; Stefano Necozione; Maurizio Guido; Roberto Rulli; Ilaria Fantasia (IMR Press, 2023)
Background: The accuracy of third-trimester ultrasound in detecting large for gestational age and macrosomic fetuses in diabetic and non-diabetic pregnant women is unclear in the literature. The aim of the study is to examine the precision of the 4-parameter Hadlock formula for the prediction of large fetuses in these two populations. Methods: A systematic review and meta-analysis were performed, and only studies evaluating the accuracy of third-trimester ultrasound using the 4-parameter Hadlock formula were included. Data were extracted, and the meta-analysis was performed using STATA software and Meta-disk 2.0 aiming to obtain the pooled sensitivity and specificity. Quality assessment of the risk of bias was performed using the QUADS-2 tool. Results: Nine articles were included in the final analysis together with 24,693,702 pregnancies screened and 2336 real large fetuses. The included articles were judged to be at high risk of bias in more than half of the cases and at doubtful risk in the remaining cases. Comparison between diabetic and non-diabetic populations was impossible because the studies considered mixed pregnancies (diabetic and non-diabetic) or only healthy, so the comparison was made between the latter two groups. The pooled sensitivity was 0.54 (95% confidence interval (CI): 0.40-0.68), and the pooled specificity was 0.94 (95% CI: 0.90-0.97). The heterogeneity estimated by the Bivariate I2 was 0.92, and the area under the summary Receiver Operating Characteristics curve was 0.19. The subgroup analysis revealed a higher level of heterogeneity for the mixed group (I2 = 0.92) and a lower one for the healthy group (I2 = 0.67). The relative sensitivity between the mixed population and the healthy one was 0.85 (95% CI: 0.49-1.45; p = 0.57), and the relative specificity between the mixed population and the healthy one was 0.98 (95% CI: 0.91-1.04; p = 0.54), the difference between healthy and mixed groups was not significant (p = 0.11). Conclusions: Despite the high heterogeneity of the data, the overall accuracy of ultrasound is similar in mixed and healthy populations and is overall moderate in predicting large fetuses.